Extending the Cooperative Phenotype: Assessing the Stability of Cooperation across Countries - Reigstad, Amanda G.; Strømland, Eirik A.; Tinghög, Gustav (Frontiers in Psychology, 2017)
This paper studies whether individual cooperation is stable across settings and over time. Involving more than 7,000 subjects on two different continents, this study documents positive correlation in cooperative behavior across economic games in Norway, Sweden, Austria and the United States. The game measures also correlate with a tendency to make deontological judgments in moral dilemmas, and display of general trust toward strangers. Using time-variation in the data, we test whether temporal stability of behavior is similar in the United States and Norway, and find similar stability estimates for both the American and Norwegian samples. The findings here provide further evidence of the existence of a stable behavioral inclination toward prosociality – a “cooperative phenotype,” as it has recently been termed. Also in line with previous research, we find that punishment and cooperation seem to be uncorrelated.